Agricultural dust exposures and health and safety practices among western australian wheatbelt farmers during harvest - Rumchev, Krassi; Gilbey, Suzanne; Mead-Hunter, Ryan; Selvey, Linda; Netto, Kevin; Mullins, Ben (MDPI, 2019)
Background: Agricultural farmworkers are routinely exposed to high levels of airborne dust particles that have been linked to adverse health outcomes.